Methods of Determination of Sum of Flavonoids in Herbal Products by Spectrophotometric Methods - Hudz, Nataliia; Nikolaieva, Nataliia; Konyk, Chrystyna; Kaplun, Ivanna; Šimková, Jana; Grygorieva, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Flavonoidcontaining plants attract the attention of researchers due to their prospect in obtaining food products and medicines with various pharmacological effects (anti-inflammatory, vessel protective, choleretic, hepatoprotective, radioprotective, antitumor, immunomodulatory, antimicrobial effects, etc.). For determining the total content of flavonoids, the method of differential spectrophotometry with a reagent of aluminum chloride is the most often used based on the complex formation of aluminum with the C-4 keto group and the hydroxyl groups of C-3 and C-5, as well as other hydroxyl groups of the flavonoid rings A and/or B. As compensation solution is used a mixture which contains the same components as the test solution, with the exception of aluminum chloride, the volume of which is replaced by the solvent on which aluminum chloride was prepared. Such a modification makes it possible to exclude the influence of colored compounds on the results of the analysis. On the basis of literary data and own research, practical approaches for methods of determining the total content of flavonoids and the identification of the dominant group of flavonoids are given. The optical density of the reaction mixture of an extract with 1 ml of a 2% solution of aluminum chloride hexahydrate should be in the range from 0,1 to 1,0 using 1 ml of the extract or its appropriate dilution. For each plant, it is necessary to set the time of stability of flavonoids with aluminum chloride. In the process of own research, this complex was stable for 65–95 minutes. The study of the total content of flavonoids should be carried out with the identification of the dominant group of flavonoids by determining the maximum absorption in the differential spectrum of the extract with 1 ml of a 2% solution of aluminum chloride. The maximum absorption is also required to select an analytical marker with an identical maximum of absorption of its complex with aluminum chloride in an identical solvent. Spectrometric studies should be supplemented by chromatography to confirm the correct choice of analytical marker.